IMPLEMENTASI PERATURAN DAERAH NOMOR 6 TAHUN 2020 TENTANG PENANGGULANGAN KEMISKINAN DI KABUPATEN TRENGGALEK - Nurul Rezqie Septia Astar; Teguh Pramono; Ajie Hanif Muzaqi (REFORMASI, 2023)
This study aims to describe the phenomenon and analyze the implementation of the policy of Regional Regulation Number 6 of 2020 concerning Poverty Reduction in Trenggalek Regency as well as to analyze the factors that are obstacles that affect it, using a qualitative descriptive type of research. Data analysis uses four stages, namely data collection, data condensation, data presentation, and drawing conclusions. The results of the research show that the implementers and the community have understood the aims and objectives of this policy well. Human resources are sufficient. Budget resources and infrastructure are still limited and there are still many problems related to poverty data. The character of the implementing agency is supported by a solid team structure involving all agencies and various parties. The attitude or tendency (disposition) of policy implementers is good enough where implementers understand and carry out their duties according to the mandate of the regional regulation. Inter-Organizational Communication and Implementing Activities have been running quite well and effectively. The socio-economic conditions in Trenggalek Regency greatly facilitate and support the implementation of this policy. The constraining factors are the existence of budget constraints, there are still inclusion errors and exclusion errors as well as problems related to the population of the poor. In addition, there are still limited supporting facilities and infrastructure as well as the mindset of the people who still tend to rely only on assistance from the government.AbstrakPenelitian ini memiliki tujuan untuk menggambarkan fenomena dan menganisa implementasi kebijakan Peraturan Daerah Nomor 6 Tahun 2020 tentang Penanggulangan Kemiskinan di Kabupaten Trenggalek sekaligus untuk menganalisa faktor yang menjadi kendala yang mempengaruhinya, dengan menggunakan jenis penelitian deskriptif kualitatif. Analisa data menggunakan empat tahapan yaitu pengumpulan data, kondensasi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Para implementator dan masyarakat telah memahami maksud dan tujuan dari kebijakan ini dengan baik dan sumber daya manusia sudah memadai. Sementara itu, sumber daya anggaran dan sarana prasarana masih terbatas dan masih terdapat banyak masalah terkait data kemiskinan. Di sisi lain karakter agen pelaksana didukung oleh struktur tim yang solid dengan melibatkan seluruh instansi dan berbagai pihak sementara dari sikap atau kecenderungan (Disposition) para pelaksana kebijakan sudah dah memahami dan melaksanakan tugas-tugasnya sesuai amanat peraturan. Komunikasi yang terjalin antar organisasi dan aktivitas pelaksana berjalan dengan cukup baik dan efektif. Namun masih terdapat kendala yaitu terbatasnya anggaran dalam kebijakan ini karena masih terdapat inclusion error dan exclusion error serta adanya masalah terkait kependudukan warga miskin.